Interleukin 10 (IL-10) influences autoimmune response in primary Sjogren's syndrome and is linked to IL-10 gene polymorphism. (2002)
To investigate the association between serum levels of interleukin 10 (IL-10), the synthesis of autoantibodies, salivary gland disease activity, clinical manifestations, and IL-10 microsatellite polymorphism in patients with primary Sjögren's syndrome (pSS).